Анализ применения гидроприводов в трансмиссиях колесных тракторов Харьковского тракторного завода - Самородов, Вадим Борисович; Аврунин, Григорий Аврамович; Мороз, Ирина Ивановна (НТУ "ХПИ", 2017)
Проведен анализ способов гидравлического управления и смазки узлов трения серийной ступенчатой трансмиссии колесных тракторов Харьковского тракторного завода (АО «ХТЗ») и разработанных кафедрой автомомобиле- и тракторосторения национального технического университета «Харьковский политехнический институт» (НТУ ХПИ) двухпоточных гидрообъемно-механических трансмиссий (ГОМТ).

The analysis of methods of hydraulic management and greasing of knots of friction of serial step transmission of the wheeled tractors of KHTZ is conducted and worked out by the department of car-and traktor building of «National Technical University Kharkiv Polytechnic Institute» (NTU KHPI) double-flux by hydromechanical volume transmissions of type of GOMT, providing the transmission of power from сombustion engine to the wheels with the stepless speed mode of motion of tractor. The hydraulic fundamental charts of management and transmission of power of transmissions are considered, and also methodologies of calculation of expense of working liquid are offered on greasing of knots of friction and losses.
Analisis of application of hydraulic fluid power in transmissions of the wheeled tractors of Kharkov tractor plant
Keywords: гидропривод объемный; насос; гидромотор; жидкость рабочая; система смазки; система охлаждения; hydraulic fluid power; pump; hydraulic motor; working fluid; systems of greasing; systems of cooling